2011
DOI: 10.1016/j.bcp.2011.01.024
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive understanding of thioTEPA metabolism in the mouse using UPLC–ESI-QTOFMS-based metabolomics

Abstract: ThioTEPA, an alkylating agent with anti-tumor activity, has been used as an effective anticancer drug since the 1950s. However, a complete understanding of how its alkylating activity relates to clinical efficacy has not been achieved, the total urinary excretion of thioTEPA and its metabolites is not resolved, and the mechanism of formation of the potentially toxic metabolites S-carboxymethylcysteine (SCMC) and thiodiglycolic acid (TDGA) remains unclear. In this study, the metabolism of thioTEPA in a mouse mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Recent studies have demonstrated the power of mass spectrometry-based metabolomics to profi le metabolic pathways to reveal the mechanism of action of nuclear receptors and the metabolic fate of drugs (9)(10)(11)(12). Metabolomics has revealed the downregulated tryptophan-nicotinamide pathways following Wy-14,643 treatment ( 9 ) and the decreased excretion of carnitine-conjugated metabolites by fenofi brate treatment in humans ( 13 ).…”
Section: Identifi Cation and Quantitation Of Urinary And Serum Metabomentioning
confidence: 99%
“…Recent studies have demonstrated the power of mass spectrometry-based metabolomics to profi le metabolic pathways to reveal the mechanism of action of nuclear receptors and the metabolic fate of drugs (9)(10)(11)(12). Metabolomics has revealed the downregulated tryptophan-nicotinamide pathways following Wy-14,643 treatment ( 9 ) and the decreased excretion of carnitine-conjugated metabolites by fenofi brate treatment in humans ( 13 ).…”
Section: Identifi Cation and Quantitation Of Urinary And Serum Metabomentioning
confidence: 99%
“…Metabolomics has been evolving as an important tool to study drug metabolism, and has been applied in the study of several drugs, such as N , N ′, N ″-triethylenethiophosphoramide (ThioTEPA) [14] and arecoline [15]. Compared with traditional metabolite identification methods, metabolomics can yield the full spectrum of metabolites, even those with relatively low abundance, which facilitates the elucidation of novel metabolic pathways [16].…”
Section: Introductionmentioning
confidence: 99%
“…1921 However, not to be overlooked, the use of conventional approaches including radiolabeled tracers 22 as well as making use of naturally occurring isotopes, such as 37 Cl, have been instrumental in helping to detect and identify drug metabolites. 5, 6 In this report, we hypothesized that stable isotope- and mass spectrometry-based metabolomics may simultaneously facilitate a better understanding of both the drug metabolism route as well as to identify endogenous biomarkers of drug action (Figure 1). To accomplish this, ultraperformance liquid chromatography coupled with electrospray ionization quadrupole time-of-flight mass spectrometry (UPLC-ESI-QTOFMS)-based metabolomics combined with multivariate data analysis (MDA) was employed to analyze the metabolites generated from tempol and deuterated tempol and the impact of tempol on endogenous metabolism.…”
Section: Introductionmentioning
confidence: 99%